Circadian Rhythms, the Mesolimbic Dopaminergic Circuit, and Drug Addiction. (2007) - McClung, Colleen A.
Abstract : Drug addiction is a devastating disease that affects millions of individuals worldwide. Through better understanding of the genetic variations that create a vulnerability for addiction and the molecular mechanisms that underlie the progression of addiction, better treatment options can be created for those that suffer from this condition. Recent studies point to a link between abnormal or disrupted circadian rhythms and the development of addiction. In addition, studies suggest a role for specific genes that make up the molecular clock in the regulation of drug sensitivity, sensitization, and reward. The influence of circadian genes and rhythms on drug-induced behaviors may be mediated through the mesolimbic dopaminergic system. This system has long been implicated in the development of addiction, and recent evidence supports a regulatory role for the brain's central pacemaker and circadian gene expression in the regulation of dopaminergic transmission. This review highlights the association between circadian genes and drug addiction, and the possible role of the mesolimbic dopaminergic system in this association.